Державне регулювання аграрного кредитування в Наддніпрянській Україні в ХІХ – на початку ХХ ст.: сучасний науковий дискурс - Зайченко, В. В.; Попов, В. М.; Zaichenko, V.; Popov, V. (ЦНТУ, 2021)
Стаття присвячена дослідженню сучасного наукового дискурсу стосовно історії державного регулювання кредитних відносин в Наддніпрянській Україні в ХІХ – на початку ХХ ст. Досліджено й проаналізовано три групи праць сучасних українських учених, зокрема дослідження, присвячені видатним економістам – теоретикам кредитування ХІХ – початку ХХ століття; праці з історії Селянського і Дворянського банків, відділення і контори яких діяли на території українських губерній; дослідження кооперативного кредитування. Доведено, що незважаючи на значну кількість наукових студій з історії кредитування в Наддніпрянській Україні в другій половині ХІХ на початку ХХ століття, у тому числі й аграрного кредитування, сьогодні переважають праці, які розкривають лише окремі аспекти цієї складної і важливої наукової проблеми без належної кооперації між представниками різних галузей знань. The purpose of the article is to consider the modern scientific discourse on agricultural lending in Naddnieper Ukraine in the second half of the 19th and early 20th centuries and to identify promising areas for further research on this issue. The authors used empirical and theoretical methods of scientific research in particular methods of analysis and synthesis, the method of scientific abstraction, and others characteristic methods of research on economic history to achieve this goal and implement the corresponding research tasks. In recent years, a body of diverse scientific research of historians, economists and lawyers has appeared in Ukraine in which these problems are considered. These works differ both in the depth of study of the problem of agricultural lending and in the range of studied issues. The entire body of works of modern Ukrainian scientists, which forms the modern scientific discourse on the history of agricultural lending in Naddnieper Ukraine in the second half of the 19th - early 20th century, consists of three groups including in particular : 1) research, which are devoted to outstanding economists and theorists of lending of the 19th - early 20th century; 2) works on the history of the Peasant and Noble banks, branches and offices of which operated on the territory of the Ukrainian governorates; 3) research of cooperative crediting. We are obliged to note that despite a significant amount of scientific research on the history of lending (including agricultural lending) in Naddnieper Ukraine in the second half of the 19th and beginning of the 20th century, today prevail works devoted only to certain aspects of this complex and important scientific problem, without proper cooperation between representatives of various branches of knowledge. In the authors' view, synectics that is scientific cooperation of representatives of various specialties: economists, historians and lawyers, should become promising in studying the history of agricultural lending in Naddnieper Ukraine in the second half of the 19th and early 20th centuries. It allows to solve such a complex scientific problem comprehensively and considering the economic component (determination of the most optimal scientifically grounded lending methods) and the historical as well as anthropological approach and the study of the legal regulation of credit relations. In our opinion, it is exactly the kind of approach, that allows not only to study the problem of the history of agricultural lending in Naddnieper Ukraine in the second half of the 19th and early 20th century comprehensively, but also to offer modern lenders a mechanism for developing balanced and affordable credit products that will stimulate the development of the agricultural sector and the economy of Ukraine as a whole.
State Regulation of Agricultural Lending in Naddnieper Ukraine in the 19th - early 20th Centuries: Modern Scientific Discourse
Keywords: аграрне кредитування; уряд; кредитна політика; банк; кооператив; теорія кредитування; agricultural lending; government; credit policy; bank; cooperative; theory of lending